Common variants in the COL4A4 gene confer susceptibility to lattice degeneration of the retina. - Akira Meguro (Public Library of Science (PLoS), 2012)
Lattice degeneration of the retina is a vitreoretinal disorder characterized by a visible fundus lesion predisposing the patient to retinal tears and detachment. The etiology of this degeneration is still uncertain, but it is likely that both genetic and environmental factors play important roles in its development. To identify genetic susceptibility regions for lattice degeneration of the retina, we performed a genome-wide association study (GWAS) using a dense panel of 23,465 microsatellite markers covering the entire human genome. This GWAS in a Japanese cohort (294 patients with lattice degeneration and 294 controls) led to the identification of one microsatellite locus, D2S0276i, in the collagen type IV alpha 4 (COL4A4) gene on chromosome 2q36.3. To validate the significance of this observation, we evaluated the D2S0276i region in the GWAS cohort and in an independent Japanese cohort (280 patients and 314 controls) using D2S0276i and 47 single nucleotide polymorphisms covering the region. The strong associations were observed in D2S0276i and rs7558081 in the COL4A4 gene (Pc = 5.8 × 10(-6), OR = 0.63 and Pc = 1.0 × 10(-5), OR = 0.69 in a total of 574 patients and 608 controls, respectively). Our findings suggest that variants in the COL4A4 gene may contribute to the development of lattice degeneration of the retina.